2000
DOI: 10.1128/iai.68.4.1928-1933.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cell Vacuolation, a Manifestation of the El Tor Hemolysin of Vibrio cholerae

Abstract: Culture supernatants of nontoxigenic nonepidemic clinical strains of Vibrio cholerae belonging to diverse serogroups were found to induce vacuolation of nonconfluent HeLa cells. The vacuoles became prominent 18 h after introduction of culture supernatant, and vacuolated cells survived for 48 h and then died. Only a fraction of the vacuolated cells took up neutral red dye, implying that there were differences in the vacuolar microenvironment. Further tests showed that the factor responsible for vacuolation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 26 publications
4
48
0
1
Order By: Relevance
“…As deduced from the results of the cytotoxicity inhibition assay on Vero cells, El Tor hemolysin was responsible for the cytotoxic activity. Furthermore, the diluted culture supernatants of the Tucumán strains caused a vacuolization effect similar to that described recently in association with El Tor hemolysin (7,21). This effect was also abolished by incubation with the corresponding antiserum.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As deduced from the results of the cytotoxicity inhibition assay on Vero cells, El Tor hemolysin was responsible for the cytotoxic activity. Furthermore, the diluted culture supernatants of the Tucumán strains caused a vacuolization effect similar to that described recently in association with El Tor hemolysin (7,21). This effect was also abolished by incubation with the corresponding antiserum.…”
Section: Discussionsupporting
confidence: 53%
“…They also demonstrated that these strains exhibited cytotoxic activity, caused by El Tor hemolysin of V. cholerae, which evoked a unique vacuolating effect on Vero cells (7). This effect of El Tor hemolysin was also observed in a group of isolates of V. cholerae non-O1 recovered in India (21), suggesting that this virulence factor may play an important role in the development of diarrhea, especially in strains lacking other well-defined toxins, e.g., CT.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Evidence of the inflammatory response due to a V. cholerae O1 El Tor strain from which all known toxin genes excluding the rtx gene cluster have been deleted has also been reported (16). The vacuolating activity of the V. cholerae El Tor hemolysin in nucleated mammalian cells may be associated with gastrointestinal symptoms caused by nontoxigenic V. cholerae (11). A recent investigation (4) demonstrated that the RTX toxins of V. cholerae caused actin depolymerization and cross-linking in HEp-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that VCH induces vacuolation in tissue culture cells (6,17,18). Therefore, it seems likely that the vacuolating activity is provoked by VCH-mediated pore formation.…”
mentioning
confidence: 99%